Soft Multiset and its Application in Information System - A. M. Ibrahim, H.M. Balami (International Journal of Scientific Research and Management (IJSRM), 2013)
The theory of soft set and multiset are vital mathematical tools used in handling uncertainties about vague concepts. In 1999, Molodtsov proposed the theory of soft set as a general frame work for dealing with indefinite, abstract idea. This paper we shall present the application of soft multiset in information systemand show that every soft multiset is a multi value information system.